Política linguística e o ensino do português como língua estrangeira (PLE): uma investigação sob a perspectiva da pragmática - Borges, Érika Gonçalves (2015)
The aim of this work was to investigate the language politics adopted in Brazil, concerning the teaching of Portuguese as a Foreign Language (PFL), and discuss its effects on the reception of international exchange students in undergraduate and graduate courses, at a Federal University in Minas Gerais. A documentary and a field research of qualitative nature was carried out in order to investigate the politics of representation regarding the PFL and the processes of identification of foreign students with the referred language, as well as the possible impacts that a \"shy\" PFL teaching policy may have in relation to the identification processes of foreign students with the portuguese language. Data was gathered through questionnaires and interviews with students, teachers and the coordinator of a portuguese course held during two semesters at the referred university. The hypothesis that guided our research was partly confirmed, at least in regards to the institution investigated. We noted that the lack of a clearly established policy for the PFL teaching seemed to make it difficult for foreign students to develop an identification process with the portuguese language. Data also showed that, due to the new status of the English language in the world, Brazil s current language politics has taken the language as an intermediary tool for the reception of foreign students and, consequently, there has not been a clearly established policy for PFL teaching.